UJI BEDA ANALISIS KINERJA KEUANGAN SEBELUM DAN SAAT PANDEMI COVID-19 PADA AGEN LPG 3 KG BERSUBSIDI PUSKOPPOLDA JATENG - Ramadhani, Pramila Gita; Setiawati, Ira; Meiriyanti, Rita (STIE PENA, 2023)
This research aims to find out and analyze whether there are differences in financial performance before and during Covid-19 at the Central Java Puskoppolda 3KG LPG Agent in the period 2016 – 2021. The population in this study is the Central Java Puskoppolda Subsidized 3KG LPG Agent and the sample that has been determined in this research is namely sales data, profit and loss data and balance sheets from the financial section of the Subsidized 3KG LPG Agent Puskoppolda Central Java in the observation period, namely 2016-2018 before the pandemic and 2019-2021 during the Covid-19 pandemic. The type of data used in this research is comparative quantitative data by using a different test sourced from company publication documentation in the form of financial reports for the Subsidized 3Kg LPG Agent Puskoppolda Central Java. The findings in this research are that there is no significant difference between the financial performance of the 3kg LPG Agent before and during the Covid-19 pandemic in the current ratio (CR), there is no significant difference between the financial performance of the 3kg LPG Agent before and during the Covid-19 pandemic in total asset turn over (TATO), there is no significant difference between the financial performance of the 3kg LPG Agent before and during the covid-19 pandemic in debt to equity ratio (DER) and there is no significant difference between the financial performance of the 3kg LPG Agent before and during the covid pandemic -19 on return on assets (ROA). Keywords: Covid-19, Current Ratio, Total Asset Turn Over, Debt to Equity Ratio, Return on Assets